Filogeografia e história demográfica de tabebuia serratifolia e tabebuia ochracea (bignoniaceae), duas espécies arbóreas neotropicais - Vitorino, Luciana Cristina (2015)
There is strong evidence that the Neotropical vegetation has been influenced by climate changes at the end of the Tertiary and Quaternary. The response of vegetation to the cold weather and dry these periods, consistent with the occurrence of the last glacial maximum, still remains in debate. It is suggested that the areas currently occupied by the Cerrado and seasonal forests (SDTFs) are remnants of a continuous vegetation that existed in the past. From the perspective of that species widely distributed in savannas and Brazilian SDTFs could help unravel the role of climate change Pleistocene on the current distribution pattern of genetic diversity in these vegetation types, we sampled 17 populations of Tabebuia serratifolia in SDTFs and 24 populations Tabebuia ochracea in savannas and sequenced intergenic non-coding regions of chloroplast (psbA-trnH, trnG-trnS e trnC-ycf6) as well as the nuclear region ITS (nrDNA). Later, we used coalescent analysis, Ecological Niche Modeling techniques (ENM) and simulations of demographic hypothesis for these species in an attempt to broaden the understanding of the changes undergone by neotropical landscape during the last ice age cycles. The sampled populations for both species showed high genetic diversity for both markers (hcpDNA = 0.8731 and hnrDNA = 0.7723 - T. serratifolia and hcpDNA = 0.927 and hnrDNA = 0.637 - T. ochracea), and large structure (Fst(cpDNA) = 0.528, P < 0.001 and Fst(ITS) = 0.742, P < 0.001 - T. serratifolia and Fst(cpDNA) = 0.742, P < 0.001 and Fst(ITS) = 0.544, P < 0.001 - T. ochracea). The coalescing analysis showed the time to the most recent common ancestor between haplotypes of the sampled populations, oldest to T. serratifolia (~ 3.4 Ma - 95% CI 1.9 - 6.8), which for T. ochracea (~ 1.9 Ma - 95% CI 0.1 - 2.3). The two species show standard recent population expansion and the niche modeling revealed for the T. serratifolia a higher potential distribution area during Holoceno medium while for T. ochracea the highest suitability area was predicted for maximum glacial last (LGM - 21ka), going in favor the hypothesis that the savannas and STDFs have submitted in the past, a wider distribution than currently known.